2016
DOI: 10.1002/jobm.201600291
|View full text |Cite
|
Sign up to set email alerts
|

Construction and application of a gene silencing system using a dual promoter silencing vector in Hypsizygus marmoreus

Abstract: As efficient reverse genetic tools are lacking, molecular genetics research has been limited in Hypsizygus marmoreus. In this study, we firstly constructed a gene-silencing method using a dual promoter vector (DPV) which was driven by gpd and 35 S promoters. The DPV was introduced into H. marmoreus via a simple electroporation procedure and the highest silenced rate of ura3 gene was 76.6%, indicating that the DPV might be suitable for gene silencing in basidiomycete. In this silencing system, the endogenous or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…For example, Volvariella volvacea produces multiple forms of extracellular laccase when grown in specific culture conditions, and some laccase genes may play an important role in the development of fruiting bodies ( Chen et al, 2003 ; Lu et al, 2015 ). Studies have found that amplifying the operation of laccase stimulates the initiation of H. marmoreus primordia and elevates the production of fruiting bodies ( Zhang et al, 2015b ; Zhang et al, 2016 ). Organisms’ carbohydrate metabolismrely heavily on lignocellulolytic enzymes, which are crucial for the transformation of the lignocellulolytic matrix during fungal growth and serve as a necessary physiological function ( Elisashvili et al, 2002 ; Bánfi et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Volvariella volvacea produces multiple forms of extracellular laccase when grown in specific culture conditions, and some laccase genes may play an important role in the development of fruiting bodies ( Chen et al, 2003 ; Lu et al, 2015 ). Studies have found that amplifying the operation of laccase stimulates the initiation of H. marmoreus primordia and elevates the production of fruiting bodies ( Zhang et al, 2015b ; Zhang et al, 2016 ). Organisms’ carbohydrate metabolismrely heavily on lignocellulolytic enzymes, which are crucial for the transformation of the lignocellulolytic matrix during fungal growth and serve as a necessary physiological function ( Elisashvili et al, 2002 ; Bánfi et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Polysaccharide is one of the main components of H. marmoreus. Studies on PHM mainly focused on biological activities, such as antitumor (Yasukawa et al, 1994), immune enhancer (Zhang et al, 2015a), antivirus (Song et al, 2013), antioxidation (Liu et al, 2018;Huang et al, 2015) and antibacterial (Xing et al, 2007) properties through molecular structural characteristic (Lingyun, 2014), extraction (Zhang et al, 2017a;2017b;Harada et al, 2005) and component analyses (Tao et al, 2007) to date. However, the study on the chelation of PHM and microelement has not been reported in the literature.…”
Section: Introductionmentioning
confidence: 99%